PERANCANGAN SISTEM INFORMASI E-COMMERCE BUSSINES TO CUSTOMER PADA DEN’S STORE - Teguh Yulfiana Riswanda; . Nurasiah (Universitas Insan Pembangunan Indonesia, 2017)
ABSTRACTThe rapid advancement of information technology in accordance with the needs of almostevery aspect is very important for our lives. There is now a requirement that informationtechnology can provide convenience in finding the desired information, reduces errorscaused by human negligence and use data more efficiently, use of information technology isoptimal in a company will support the efficiency and effectiveness of work in data processingfor obtain information dibutuhkan.dalam this study can be formulated, how the system runson the den''s store, how to design systems sales information on the den''s store. So that thetopic does not deviate from the topic existing problems in the den''s store. The authors makethe boundary problem in research among other things, the payment system using the accounttransfer between banks, a system built only product sales process, the system discussed is aretail and wholesale, software used Notepad ++ with MySQL data base. The purpose of theauthors conducted a study is, to know the sales information system on the den''s store, to makesales information system design at Den''s store. The research method using descriptiveanalysis method, the results obtained using the sales information system Making E-commerceeasier for customers to make buying and selling without having to come into place. Thebenefits of implementing the use of E-commerce, will provide an overview of how the salessystem engineering required in the face of competition in the era of globalization. Salesinformation system on Den''s store is expected to be an alternative in the promotion andpurchase transactions more easily effectively and efficiently. Based on the results of researchconducted by the author regarding the sales information system has been described inprevious chapters, the writer can draw a conclusion, System currently running on the den''sstore is a conventional system in the sense that prospective buyers have come to the den''sstore itself, and information the goods are still lacking ter uptudate, With the implementationof this system is expected to facilitate the performance of the administrator or owner of thedata gathering process because it has an integrated database, it is very effective and efficientfor the performance of administrators.Keywords:E-commerce, effectiveness, efficiency, promotion of transactions.